Effect of E-Service Quality, Value, and Satisfaction on Young Indian Consumers’ Online Purchase Intention - Jain, Reetika; Aggarwal, Amita (Indian Journal of Marketing, 2026)
Purpose and Originality Value : The period of the late 1990s and the early 2000s was marked by increased access to the internet by people globally and the development of new businesses in the online space. Online shopping emerged as a novel retail business offering attributes like the ease of use of a website, privacy, security, customer services, and immediate availability of product comparison and review by past users. Consequently, electronic service quality (ESQ) became an important determinant of customer satisfaction (CS) and loyalty in the online marketplace. While the structural relationships among ESQ, perceived value (PV), satisfaction, and behavioral intentions (BI) have been widely examined in developed markets, their relative strengths and mediating mechanisms remain context-specific in emerging digital economies. India represents a distinctive e-commerce environment characterized by high price sensitivity, intense platform competition, low switching costs, mobile-first usage patterns, and a demographically young consumer base. The contextual factors may alter the salience of PV and satisfaction relative to service quality, thereby warranting focused empirical examination rather than direct generalization from developed-market evidence. Methodology : This study is based on online survey responses from over 647 respondents based in India. Quantitative research methods were employed to test hypothesized relationships using confirmatory factor analysis and structural equation modeling on the reliable and valid measurement scales adopted in this study. ANOVA was employed to assess demographic differences in online shopping attitude and intention. Findings and Implications : The results of this study concluded that the quality of e-services and PV had a significant positive effect on CS, which in turn impacted the BI. The findings of this study offer contextual insights into the interplay between ESQ, PV, satisfaction, and BI among digitally literate online consumers in India, with implications primarily relevant for young and early-adopter segments of the e-commerce market.